Collaborative Innovation Network, Knowledge Base, and Technological Innovation Performance-Thinking in Response to COVID-19 - Jialu, Su; Zhiqiang, Ma; Binxin, Zhu; Haoyang, Xie; Fredrick Oteng, Agyeman; Hu, Weijun (Frontiers in Psychology, 2021)
In the midst of the COVID-19 crisis, the collaborative innovation network of enterprises is conducive to the sharing of innovation resources, knowledge transfer, and technology diffusion, which is closely related to the improvement of corporate technological innovation performance. Based on the patent application data of listed companies in Jiangsu, Zhejiang, and Shanghai, this paper constructs a cooperation matrix, describes the characteristics of collaborative innovation network from two dimensions of network structure and network relationship, introduces the width of the knowledge base as a moderating variable, and analyzed the nexus between characteristics of a collaborative innovation network and technological innovation performance. Based on the panel data of 193 listed companies in Jiangsu, Zhejiang, and Shanghai, this paper uses a multiple linear regression model for empirical analysis. The results show that there is a U-shaped relationship between agglomeration coefficient and technological innovation performance; the width of the knowledge base strengthens the positive relationship between the structural hole and technological innovation performance, while the width of the knowledge base weakens the positive relationship between network relationship strength and technological innovation performance. The findings will enhance enterprises to participate in a suitable collaborative innovation according to their knowledge-based characteristics and improve the performance of technological innovation.